Propensity of bed materials used in dual fluidized beds to retain ash-forming elements from biomass fuels - Folkeson, Björn (2014)
The main aim of this work was to investigate the propensity of bed materials to retain ash-forming elements from biomass under conditions relevant to dual fluidized bed gasification (DFBG). The investigation was carried out in a laboratory-scale bubbling fluidized bed reactor in which biomass was gasified with steam and the unconverted char was combusted in the temperature range 800–900 ° C. Three bed materials (sand, olivine and bauxite) and two biomass fuels (forestry residue and wheat straw) were studied. From the results obtained and literature on the ash transformation chemistry during thermal conversion of biomass, it was found that the extent to which ash-forming elements from biomass are retained on bed materials depend among other factors on (1) the abundance of ash-forming elements in the fuel, (2) the ability of the bed material to react and form compounds with ash-forming elements and (3) the atmosphere surrounding the fuel in the reactor. For example, Ca, P and K (which were among the most abundant ash-forming elements in the forestry residues) were also the main ashforming elements retained on sand, olivine and bauxite during thermal conversion of the forestry residues. However, the retention of these elements differed on the three bed materials. With respect to reactor atmosphere, Ca and P were retained on olivine primarily during char combustion while the retention of K on olivine was somewhat similar during gasification and char combustion.